Fa’āliyyah Istikhdām Kahoot fī Ta’līm Mahārah al-Istimā’ ‘an Bu’d Ladā Talāmīdh Madrasah Ruḥamā’ al-Mutawassiṭah al-Islāmiyyah Tanggerang - Muslimin, Muhamad Ihwanul; Nurrasyid, Hadi; Ridlo, Ubaid (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
This research/paper aims to reveal the results of the tests that use the Kahoot App for the students and do not use it, and to reveal the effectiveness of the Kahoot method in teaching he remote listening skill. This research followed a semi-experimental study based on the quantitative approach, and its design consisted of the experimental group and the control group. The researcher used data collection methods, which are direct observation, personal interview, tests and questionnaires. After the researcher analyzed the data, reached the mean of the two tests, the pre-test and the post-test. Based on the average results of the experimental group at a value of 28.75 and the average results of the control group at a value of 16.75, it indicates that the average results of the experimental group are greater than the average results of the control group. And I came to the analysis of the data using the "t" test rule. The result of the arithmetic t0 (t0) is 2.79, so the table is at the level of significance of 5% on the value of 1,686 and the level of significance of 1% on the value of 2,429, and this indicated that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) accepted. This means that the use of the Kahoot method in teaching the remote listening skill of the pupils of this school is statistically significant. يهدف هذا البحث إلى الكشف عن نتائج الاختبارات التي استخدم فيها تطبيق كاهوت للطلاب والذين لم يستخدموه، وكذلك للكشف عن فعالية طريقة كاهوت في تعليم مهارة الاستماع عن بعد. اتبع هذا البحث منهجًا شبه تجريبي قائمًا على النهج الكمي، ويكون تصميمه من مجموعة تجريبية ومجموعة ضابطة. استخدم الباحث طرقًا لجمع البيانات، من الملاحظة المباشرة، المقابلات الشخصية، الاختبارات، والاستبيانات. بعد أن قام الباحث بتحليل البيانات، توصل إلى متوسط نتائج الاختبارين، الاختبار القبلي والاختبار البعدي. بناءً على نتائج متوسطات المجموعة التجريبية بقيمة 28.75 ومتوسط نتائج المجموعة الضابطة بقيمة 16.75، فإن هذا يشير إلى أن متوسط نتائج المجموعة التجريبية أكبر من متوسط نتائج المجموعة الضابطة. وقام بتحليل البيانات باستخدام قاعدة اختبار "t". وكانت نتيجة t الحسابية (t0) هي 2.79، وبالتالي فإن القيمة الجدولية عند مستوى الدلالة 5% هي 1.686 وعند مستوى دلالة 1% هي 2.429، مما أشار إلى أنه تم رفض الفرضية الصفرية (H0) وقبول الفرضية البديلة (Ha). وهذا يعني أن استخدام طريقة كاهوت في تعليم مهارة الاستماع عن بعد لطلاب هذه المدرسة له دلالة إحصائية.